2022
DOI: 10.1136/bmjopen-2021-050363
|View full text |Cite
|
Sign up to set email alerts
|

’[We] learned how to speak with love’: a qualitative exploration of accredited social health activist (ASHA) community health worker experiences of the Mobile Academy refresher training in Rajasthan, India

Abstract: IntroductionMobile Academy is a mobile-based training course for India’s accredited social health activist (ASHA) community health workers (CHW). The course, which ASHAs access by dialling a number from their phones, totals 4 hours of audio content. It consists of 11 chapters, each with their own quiz, and provides a cumulative pass or fail score at the end. This qualitative study of Mobile Academy explores how the programme was accessed and experienced by CHWs, and how they perceive it to have influenced thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…An independent qualitative assessment of Mobile Academy found that the service bolstered FLHWs’ RMNCH knowledge and provided them with positive ways to communicate with families. 13 An independent analysis of system-generated call record data found that over four in five FLHWs (81%) who started Mobile Academy completed the IVR training, and only 1% did not ‘pass’ (i.e. accurately answer at least half the quiz questions) 14 suggesting the service was effective.…”
Section: Impact On Health Outcomes and Integrationmentioning
confidence: 99%
“…An independent qualitative assessment of Mobile Academy found that the service bolstered FLHWs’ RMNCH knowledge and provided them with positive ways to communicate with families. 13 An independent analysis of system-generated call record data found that over four in five FLHWs (81%) who started Mobile Academy completed the IVR training, and only 1% did not ‘pass’ (i.e. accurately answer at least half the quiz questions) 14 suggesting the service was effective.…”
Section: Impact On Health Outcomes and Integrationmentioning
confidence: 99%
“…17 18 Mobile Academy has been identified as an effective tool for refreshing FHLWs' knowledge, as well as a mechanism for modelling a more effective style of interpersonal communications. 19 Although Mobile Kunji was not scaled by the national government because it was thought that FLHWs would soon have personal smartphones, research indicated that it was associated with improvements in a range of health outcomes. 20 These results suggest that HCD processes, when effectively applied, can be invaluable in creating impactful digital solutions that resonate with communities and have a strong potential for scale, sustainability and health system integration.…”
Section: Discussionmentioning
confidence: 99%
“…Another initiative undertaken by the central government is the mobile phone-based interactive voice-based training program for the ASHAs. However, it also underlines the requirement of financial incentives to reimburse for their time spent on training (Scott et al, 2022).…”
Section: Operational/managerial Capacitymentioning
confidence: 99%
“…Besides these developments on health policy and CHWs in LMICs and India, an analytical effort that employs the PCF and seeks to understand how distinct policy capacities relate to each other has not been made yet. Prashanth et al, 2014;Scott et al, 2019;Sodhi et al, 2016;Srivastava et al, 2016 Operational capacities Improvement in the functioning of state and non-state actors Support to the frontline policy implementers Kim et al, 2017;Nambiar & Sheikh, 2016;Scott et al, 2022 Saprii et al, 2015;Wahid et al, 2020 Note. Adapted from Wu et al (2015).…”
mentioning
confidence: 99%